Kewenangan Majelis Permusyawaratan Rakyat Dalam Pemberhentian Presiden dan/atau Wakil Presiden Berdasarkan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Efendi, Febri Mahfud, Iswanto, S.H., M.H, Jaka Susila, S.H., M.Si., M.H (2016)
The amendment of 1945 Indonesian Constitution took many changes, one of them is the existence of the regulation about the dismissal of President and/or Vice President in his/her term of office (deposing). This event certainly made Indonesia becoming more determided for carrying out the law-state principle due to the involvement of Contitutional Court (Indonesian: Mahkamah Konstitusi, MK) in the decision-making process. Therefore, hopefully there would be no more dismissal of President and/or Vice President by political reason. This study aims at analysing the mechanism of dismissal the President and/or Vice President in his/her term of office (deposing), and then to interpretate the final verdict which was uses for the dismissal of the President and/or Vice President. This study is a normative legal research, using qualitative descriptive analysis, and using hermeneutics interpretation of the law. This result of this research showed that dismissal of the President and/or Vice President shall be proposed by the House of Representatives (Indonesian: Dewan Perwakilan Rakyat, DPR) to the People's Consultative Assembly (Indonesian: Majelis Permusyawaratan Rakyat, MPR). Prior to the filing of the dismissal to the People's Consultative Assembly, House of Representatives must first submit an application to the Contitutional Court. However, the mecanism of 1945 constitution bore many fissure for the dismissal of persident and/or Vice President by political reason. Where the final decision lies in the hands of People's Consultative Assembly (Indonesian: Majelis Permusyawaratan Rakyat, MPR) through the plenary meeting with the final decision comes through majority voice model.